Neither Neoplasia Nor Tuberculosis, but Francisella. (27th April 2016) - Mambie, Adeline; Wallet, Frédéric; Scherman, Laurine; Armand, Sylvie; Vervelle, Christine; Faure, Karine; Guery, Benoit; Titécat, Marie; Loïez, Caroline
Abstract: Tularaemia is an emerging anthropozoonosis transmitted by contact with infected animals and through arthropod bites, inhalation, or ingestion. We describe a pulmonary nodule suggesting cancer in a 70-year-old man. Histological analysis excluded neoplasia, and bacteriological culture excluded tuberculosis. Serological testing and PCR Francisella were positive for this hunter patient, then treated by ciprofloxacin with a favourable outcome.